Transformational Leadership in the Military’s Wartime and Peacetime - Rudy Sutanto (The Republic of Indonesia Defense University, 2025)
Leadership is a fundamental element that determines the effectiveness of an organization, both in wartime and peacetime contexts. This study aims to analyze the application of transformational leadership theory in the military context, during both periods of conflict and peace. Transformational leadership theory is considered relevant because it explains how leaders can inspire, motivate, and collectively develop their subordinates in facing dynamic challenges within the military environment. This study employs a qualitative method with a descriptive-analytical approach. Data were obtained through a literature review of various scholarly sources on leadership, military organizations, and the transformational theory developed by Bass and Avolio. The findings indicate that transformational leadership can be effectively applied in the military, both to address operational pressures during wartime and to build organizational structure and personnel during peacetime. These findings affirm that principles such as idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration significantly contribute to improving morale, efficiency, and the resilience of military organizations. However, certain limitations, such as the hierarchical structure and command culture, remain challenges in its implementation. This study recommends strengthening leadership training based on transformational values in the future development of military organizations